Phosphoproteomic Analysis Reveals a Different Proteomic Profile in Pediatric Patients With T-Cell Lymphoblastic Lymphoma or T-Cell Acute Lymphoblastic Leukemia - Veltri, Giulia; Lovisa, Federica; Cortese, Giuliana; Pillon, Marta; Carraro, Elisa; Cesaro, Simone; Provenzi, Massimo; Buffardi, Salvatore; Francescato, Samuela; Biffi, Alessandra; Buldini, Barbara; Conter, Valentino; et al. (Frontiers in Oncology, 2022)
T-cell lymphoblastic lymphoma (T-LBL) and lymphoblastic leukemia (T-ALL) arise from the transformation of precursor T-cells sharing common morphological and immunophenotypic features. Despite this, T-LBL and T-ALL show different genomic/transcriptomic profiles and whether they represent two distinct disease entities or variant manifestations of the same disease is still a matter of debate. In this work, we performed a Reverse Phase Protein Array study on T-LBL and T-ALL samples and demonstrated that they are characterized by a different phosphoproteomic profile. Indeed, T-LBLs showed the hyperactivation of FAK/ERK1/2 and AKT/mTOR pathways, whereas JAK/STAT pathway was significantly hyperphosphorylated in T-ALLs. Moreover, since the only criteria for discriminating T-LBL from T-ALL is blasts’ infiltration below 25% in the bone marrow and lymphoma patients can present with a percentage of blasts close to this cut-off, a biomarker that could help distinguishing the two diseases would be of great help for the clinical diagnosis and treatment decision. Pursuing this aim, we identified a proteomic signature of six proteins whose expression/activation was able to discriminate stage IV T-LBL from T-ALL. Moreover, we demonstrated that AKT hyperphosphorylation alone was able to distinguish stage IV T-LBL from both T-ALL and stage III T-LBL. Concluding, these data demonstrate that T-ALL and T-LBL bear different phosphoproteomic profiles, further sustaining the hypothesis of the two disease as different entities and paving the way for the identification of new biomarkers able to distinguish stage IV T-LBL from T-ALL disease, so far based only on BM involvement criteria.